Breast conserving surgery using oxidized regenerated cellulose as filling biomaterial: recommendations to improve clinical outcomes - Gianluca Franceschini (BMC, 2021)
Abstract Oxidized regenerated cellulose is considered an optimal local hemostatic agent thanks to its favorable biocompatibility, absorption characteristics and ease-of-use. Recently, oxidized regenerated cellulose has also been used as a filler in breast conserving surgery with a reconstructive purpose in order to repair partial breast defects and improve aesthetic outcomes. However, some postoperative problems due to its use, such as allergic reactions, seroma, foreign-body reaction and misdiagnosis during the follow-up of breast cancer patients, have been shown. These possible surgical complications can undermine clinical outcomes and lead to delay the beginning of oncological treatments with a negative impact on patient quality of life and survival. An adequate surgical expertise and the compliance with some specific recommendations are crucial in order to minimize postoperative issues and optimise aesthetic outcomes.